Cultural specialization and genetic diversity: Killer whales and beyond. (7th April 2020) - Whitehead, Hal
Highlights: Cultural specialization generally decreases mitochondrial genetic diversity. Cultural specialization generally decreases nuclear genetic diversity. This occurs primarily because cultural specialization reduces population size. Small group sizes increases the magnitude of these reductions. Cultural specialization may explain low genetic diversity in the killer whale. Abstract: Culturally-transmitted ecological specialization can reduce niche breadths with demographic and ecological consequences. I use agent-based models, grounded in killer whale biology, to investigate the potential consequences of cultural specialization for genetic diversity. In these models, cultural specialization typically reduces the number of mitochondrial haplotypes, mitochondrial haplotype diversity, mitochondrial nucleotide diversity, and heterozygosity at nuclear loci. The causal route of this decline is mostly indirect, being ascribed to a reduction in absolute population size resulting from cultural specialization. However, small group size exacerbates the decline in genetic diversity, presumably because of increased founder effects at the initiation of each cultural ecotype. These results are concordant with measures of low genetic diversity in the killer whale, although culturally-transmitted ecological specialization alone might not be sufficient to fully account for the species' very low mitochondrial diversity. The process may also operate in other species. Graphical abstract: Image, graphical abstract